Nel mondo sensibile: realismo empatico nella poesia italiana contemporanea (ENTHYMEMA, 2020)
The paper aims at exploring a still under-investigated strand of contemporary Italian poetry. I propose to use the aesthetic descriptor empathic realism in order to encompass it, whereby realism is interpreted in naturalistic terms and empathy is conceived of as a relationship of alignment between narrator and character(s). I analyze and compare 29 textual samples drawn from 11 authors and focus on various mimetic and narrative strategies which traditional narratology typically associates to fiction writing. A special emphasis is given to the representation of referents and to their translation into verbal images, either standalone or arranged in syntagmatic sequences. The tools of traditional stylistics are complemented by additional analytical tools which, following Gunther Kress and Teo van Leeuwen’s grammar of visual design, assume a high degree of overlap between verbal texts and images. The study concludes by listing a set of stylistic features characterizing empathic realism in recent Italian poetry.
Keywords: realism; empathy; image; descriptive focus; stylistics